Effect on Work Environment and Compensation on Employee Performance at PT. JAINDO Metal Industries in Bandung - Herry Suherman (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2021)
This study aims to determine the effect of work environment and compensation on employee performance at PT. Jaindo Metal Industries in Bandung. The method used is explanatory research with analysis techniques using statistical analysis with regression testing, correlation, determination, and hypothesis testing. The results of this study that the work environment has a significant effect on employee performance by 41.4%; hypothesis testing is obtained t count> t table or (7,020> 1,994). Compensation significantly affects employee performance by 43.8%; hypothesis testing is obtained t count> t table or (7.385> 1.994). Work environment and compensation simultaneously significantly affect employee performance with the regression equation Y = 7.895 + 0.382X1 + 0.426X2, and the contribution of the effect is 57.2%, hypothesis testing obtained count> F table or (46.042> 2.740).